Cemetery of splendour [videorecording (DVD)] - Apichatpong Weerasethakul, 1970-; Jenjira Pongpas; Banlop Lō̜mnō̜i; Rueangram, Jarinpattra (Strand Releasing Home Entertainment, 2016)
"Soldiers with a mysterious sleeping sickness are transferred to a temporary clinic in a former school. The memory filled space becomes a revelatory world for housewife and volunteer Jenjira, as she watches over Itt, a handsome soldier with no family visitors. Magic, healing, romance and dreams are all part of Jen's tender path to a deeper awareness of herself and the world around her"--Container.